Effect of Film Packaging on the Quality of Tomato Fruits under Ambient Conditions - Edusei, Vida; Cornelius, Eric William (Department of Agronomy and Horticulture, IPB University, 2015)
Polyethylene bags of different permeability were tested to extend the life of tomatoes (Lycopersicon esculentum) under ambient conditions. Tomato fruits at Breaker stage of ripening were packed in low density polyethylene bags (thickness 0.0046 mm) with four different types of perforation, i.e. without pinholes, bag with 10, 15 and 20 pinholes. All bags were stored for 21 days at 28ºC and 74% relative humidity. Fruits were evaluated for changes in colour, physical appearance, firmness and weight loss. Soluble solids content was determined at the end of storage. All unwrapped tomato fruits were red ripe 6 days after storage and after 21 days of storage fruits were soft, appeared deep red, shriveled and dusty. Fruits sealed in bags delayed red colour development, appeared glossy after 21 days of storage. Fruits sealed in polyethylene bags were significantly (p<0.05) firmer and had low weight loss than fruits stored unwrapped. Fruits sealed within polyethylene bag with 20 pinholes had the highest soluble solids content after 21 days. This study shows that storage of tomatoes in polyethylene bag under ambient condition is a promising alternative to refrigeration to reduce wastage and consequently increase the marketable life of harvested tomatoes in tropical countries.Keywords: tomatoes, storage, low density polyethylene bags, ambient conditions